Intersentential pronominal reference in child and adult language: Proceedings of the Conference on Intersentential Pronominal Reference in Child and Adult Language, December 1-2, 2006, Zentrum für Allgemeine Sprachwissenschaft (ZAS), Berlin - Bittner, Dagmar; Gagarina, Natalia (ZAS Papers in Linguistics, 2007)
The 48th volume of the ZAS Papers in Linguistics presents selected papers from the conference on Intersentential pronominal reference in child and adult language held at the ZAS in December, 2006. The conference, organized by the project Acquisition and disambiguation of intersentential pronominal reference, brought together leading researchers dealing with anaphora resolution in diverse theoretical approaches and the acquisition perspective on pronominal reference taken by the ZAS project.